节拍化疗——晚期非小细胞肺癌另辟蹊径的治疗策略 (Zhongguo Fei Ai Za Zhi, 2015)
Metronomic chemotherapy is an emerging strategy to fight cancer. Unlike traditional chemotherapy, metronomic chemotherapy is defined by the frequent, repetitive administration of chemotherapeutic drugs at relatively low doses, and without prolonged drug-free break. Initially thought to play a role inhibiting tumor angiogenesis by targeting activated endothelial cells in tumors, metronomic chemotherapy is a multi-targeted therapy, including activation of immunity, effect on tumour initiating cells, induction of tumor dormancy. It is from eradicateing tumor cells to improve effect, reduce the toxicity and improve quality of life for treatment of advanced non-small cell lung cancer (NSCLC). Metronomic chemotherapy which can avoid the toxicity of traditional chemotherapy and rebounding is explored in clinical studies of advanced NSCLC, as a promising treatment strategy.